Internalizing and externalizing symptoms in children during the COVID-19 pandemic: a systematic mixed studies review - Levante, Annalisa; Martis, Chiara; Bianco, Federica; Castelli, Ilaria; Petrocchi, Serena; Lecciso, Flavia (Frontiers in Psychology, 2023)
Introduction Given the vulnerability of children during the COVID-19 pandemic, paying close attention to their wellbeing at the time is warranted. The present protocol-based systematic mixed-studies review examines papers published during 2020–2022, focusing on the impact of the COVID-19 pandemic on children's internalizing/externalizing symptoms and the determinants thereof. Method PROSPERO: CRD42022385284. Five databases were searched and the PRISMA diagram was applied. The inclusion criteria were: papers published in English in peer-reviewed journals; papers published between January 2020 and October 2022 involving children aged 5–13 years; qualitative, quantitative, and mixed studies. The standardized Mixed Method Appraisal Tool protocol was used to appraise the quality of the studies. Results Thirty-four studies involving 40,976 participants in total were analyzed. Their principal characteristics were tabulated. The results showed that children's internalizing/externalizing symptoms increased during the pandemic, largely as a result of disengagement from play activities and excessive use of the internet. Girls showed more internalizing symptoms and boys more externalizing symptoms. Distress was the strongest parental factor mediating children's internalizing/externalizing symptoms. The quality of the studies was appraised as low (n = 12), medium (n = 12), and high (n = 10). Conclusion Gender-based interventions should be designed for children and parents. The studies reviewed were cross-sectional, so long-term patterns and outcomes could not be predicted. Future researchers might consider a longitudinal approach to determine the long-term effects of the pandemic on children's internalizing and externalizing symptoms. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022385284, identifier: CRD42022385284.